Parameter (Dawabit) Dalam Ucapan Doa Terhadap Non-Muslim: Parameter (Dawabit) In The Prosecution 0f Pray for Non-Muslim - Meerangani, Khairul Azhar; Ramli, Rushdi; Marinsah, Syamsul Azizul; Rosele, Muhammad Ikhlas (Online Journal of Research in Islamic Studies, 2018)
The diversity of Malaysian’s people creates cross-cultural and religious relationship. Interactions that occur in daily life reveal Muslim societies with various issues that require specialized guidance and assessment based on the perspective of Islamic law. Among polemics that often cause confusion among Muslims is the legal issue of praying for non-Muslims. This issue will often lead to annoyance especially to Muslims who have intimate relationships with non-Muslims. Therefore, this study aims to examine and analyze the law (ḥukm) of praying for non-Muslims in the current context in Malaysia according to Islamic perspective. The views of Muslim scholars on this issue are analyzed descriptively in producing a parameter (ḍawābiṭ) to guide the Muslim and non-Muslim relations. In summary, there are legal differences in the issue of praying for non-Muslims who are still alive and who have died. This distinction needs to be given attention by every Muslim to ensure that every word of prayer that comes out is still within the bounds of syarak.